Road of bones - Golden, Christopher (St. Martin's Press, 2022)
"Christopher Golden's Road of Bones is a stunning supernatural thriller set in Siberia, where a film crew is covering an elusive ghost story about a highway built on top of the bones of prisoners of Stalin's gulag. Kolyma Highway, otherwise known as the Road of Bones, is a 1200 mile stretch of Siberian road where winter temperatures can drop as low as sixty degrees below zero. Under Stalin, at least eighty Soviet gulags were built along the route to supply the USSR with a readily available workforce, and over time hundreds of thousands of prisoners died in the midst of their labors. Their bodies were buried where they fell, plowed under the permafrost, underneath the road. Felix Teigland, or "Teig," is a documentary producer, and when he learns about the Road of Bones, he realizes he's stumbled upon untapped potential. Accompanied by his camera operator, Teig hires a local Yakut guide to take them to Oymyakon, the coldest settlement on Earth. Teig is fascinated by the culture along the Road of Bones, and encounters strange characters on the way to the Oymyakon, but when the team arrives, they find the village mysteriously abandoned apart from a mysterious nine-year-old girl. Then, chaos ensues. A malignant, animistic shaman and the forest spirits he commands pursues them as they flee the abandoned town and barrel across miles of deserted permafrost. As the chase continues along this road paved with the suffering of angry ghosts, what form will the echoes of their anguish take? Teig and the others will have to find the answers if they want to survive the Road of Bones"--